Post-War Planning i Europe 1945-47 - Cairncross, Sir Alec (Økonomi & Politik, 2026)
Two years elapsed between the end of the war in Europe and General Marshall's speech in Harvard heralding the Marshall Plan. What happened in those two years? What problems did European reconstruction raise? How were those problems seen and by what strategies was it proposed to overcome them?